Supporting K-12 teachers in the context of whole-school sustainability: four case studies. Issue 4 (2nd October 2021) - Hurd, Emily; Ormsby, Alison A.
Abstract: We examined practices from whole-school sustainability programs in four U.S. K-12 institutions in the areas of educator values, skills, and support. Based on results from four school visits, 35 interviews, four classroom observations, and four campus tours, this study analyzes ways to support teachers with the implementation of K-12 sustainability education. Results are presented based on the following themes: educator and campus values; educator skills and challenges; and support through professional development. We provide recommendations focusing on initiatives to use the campus environment as a teaching tool, incorporate sustainability in the curriculum, and support sustainability-themed professional development initiatives.